Business formation and aggregate investment - Christian Keuschnigg (Institute for Advanced Studies (IHS), 1995)
The paper proposes an intertemporal equilibrium model with monopolistic competition and free entry to explain the nexus between business formation and medium run growth. An investment externality is identified that results in underaccumulation of capital in the decentralized market equilibrium and, thus, creates an investment multiplier. Some form of investment promotion is called for. The paper compares the effectiveness of policies to promote business formation with a general investment subsidy. – – Das Papier entwickelt ein intertemporales Gleichgewichtsmodell mit monopolitischer Konkurrenz und freiem Marktzutritt und erklärt den Zusammenhang zwischen Firmengründungen und mittelfristigen Wachstum. Es wird eine Externalität in den Investitionsentscheidungen festegestellt, die Unterakkumulation von Kapital im dezentralisierten Marktgleichgewicht herrruft und einen Investitionsmultiplikator erzeugt. Die Externalität macht Investitionsförderung notwendig. Das Papier vergleicht die relative Wirksamkeit einer allgemeinen Investitionsprämie mit einem Steueranreiz zur Förderung von Firmengründungen.
Keywords: E62; H23; L16; 330; monopolistic competition; business formation; investment multiplier; under-accumulation of capital